Pengaruh Kepemimpinan Transformasional Kepala Sekolah, Budaya Organisasi dan Motivasi Kerja terhadap Kinerja Guru SMP Negeri Se-Kecamatan Trienggadeng Kabupaten Pidie Jaya - Mursalin, Mursalin; Syarifuddin; Saputra, Rudy Juli (Singkite Journal, 2023)
This study aims to analyze and prove the influence of Principal Transformational Leadership, school organizational culture and teacher motivation on teacher performance. With the study of teachers at State Middle School, Trienggadeng District, Pidie Jaya Regency. Data collection through questionnaire instruments and quantitative analysis methods with path model statistics. The results of the study show: there is a direct and indirect effect of transformational leadership on teacher performance by 31.72%. The influence of organizational culture on teacher performance is 41.6%. And the direct and indirect influence of work motivation on teacher performance is 51.76%. The results of the determination test also explained that the contribution of the school principal's transformational leadership factors, organizational culture and work motivation to the teacher performance of Trienggadeng Public Middle School, Pidie Jaya Regency was 44.5%.